0408 Myths About Infant, Child, and Adolescent Sleep: Addressing False Beliefs That Hinder Sleep Health During These Crucial Developmental Stages. (27th May 2020) - Robbins, R; Hale, L; Beebe, D; Wolfson, A R; Grandner, M A; Mindell, J A; Owens, J; Tapia, I; Byars, K C; Gruber, R; Montgomery-Downs, H; Wise, M; et al.
Abstract: Introduction: Sleep is vital for healthy development from infancy through adolescence. Despite its importance, false beliefs that conflict with scientific evidence (myths) may be common among caregivers and impair sleep health during these crucial stages. Methods: Researchers compiled a list of potential myth statements using internet searches of popular press and scientific literature. We utilized a Delphi process with experts (n=12) from the fields of pediatric, sleep, and circadian research and clinical practice. Selection and refinement of myths by sleep experts proceeded in three phases, including: focus groups (Phase 1); email-based feedback to edit, add, or remove myths (Phase 2); and closed-ended questionnaires (Phase 3) where experts rated myths on two dimensions: (1) falseness and (2) public health significance using 5-point Likert scale: 1 ("not at all") to 5 ("extremely false/important"). Results: Thirty-two sleep myths were identified across three developmental categories: infant (14 myths), child (6 myths), and adolescent (12 myths). Mean expert ratings illuminated the most pressing myths in each developmental category: infant sleep ("Sleep training causes psychological harm, including reduced parent-child attachment:" falseness =4.7, s.d.=0.7; public health significance=4.0, s.d.=1.1); child sleep ("Heavy, loud snoring for my child means he's sleeping deeply:" falseness=4.8, s.d.=0.6; public health significance=4.7, s.d.=0.7), and teenager sleep ("Falling asleep in class means your teenager is lazy and not motivated:" falseness=4.8, s.d.=0.5; public health significance=4.3, s.d.=0.8). Conclusion: The current study identified commonly-held myths about infant, child, and adolescent sleep that are not supported by (or worse, counter to) scientific evidence. If unchecked, these myths may hinder sleep at a critical developmental stage. Future research may include public health education to correct myths and promote healthy sleep among infants, children, and teenagers. Support: 5T32HL007901